2023
DOI: 10.1038/s41598-023-37654-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of VEGF and inflammatory cytokines, modulation of Annexin A1 and organ functions by galloylquinic acids in breast cancer model

Abstract: The ongoing development of novel drugs for breast cancer aims to improve therapeutic outcomes, reduce toxicities, and mitigate resistance to chemotherapeutic agents. Doxorubicin (Dox) is known for its significant side effects caused by non-specific cytotoxicity. In this study, we investigated the antitumor activity of galloylquinic acids (BF) and the beneficial role of their combination with Dox in an Ehrlich ascites carcinoma (EAC)-bearing mouse model, as well as their cytotoxic effect on MCF-7 cells. The EAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…This is in line with other data demonstrating that STAT3 stimulates cytokines in BC and that it has been associated with poor prognosis [77]. Furthermore, the pro-inflammatory VEGF seems to be another important key player in the tumorigenesis of BC [78]. This is consistent with the finding that in up to 70% of BC cases, a dysregulation of cellular processes such as autophagy has been reported to be associated with a reduced expression of autophagy-promoting proteins due to aberrant DNA methylation, leading to increased therapy resistance [79,80] (Figure 3).…”
Section: Breast Cancersupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with other data demonstrating that STAT3 stimulates cytokines in BC and that it has been associated with poor prognosis [77]. Furthermore, the pro-inflammatory VEGF seems to be another important key player in the tumorigenesis of BC [78]. This is consistent with the finding that in up to 70% of BC cases, a dysregulation of cellular processes such as autophagy has been reported to be associated with a reduced expression of autophagy-promoting proteins due to aberrant DNA methylation, leading to increased therapy resistance [79,80] (Figure 3).…”
Section: Breast Cancersupporting
confidence: 91%
“…This is in line with other data demonstrating that STAT3 stimulates cytokines in BC and that it has been associated with poor prognosis [ 77 ]. Furthermore, the pro-inflammatory VEGF seems to be another important key player in the tumorigenesis of BC [ 78 ].…”
Section: Epigenetic Changes As Key Driving Factor Of Breast Cancer An...mentioning
confidence: 99%
“…One of the important hallmarks of cancer is angiogenesis, which can be targeted as a treatment strategy for different cancers [ 36 ]. A recent study demonstrated that a naturally occurring compound galloylquinic acid suppressed the expression of VEGF and induced cytotoxicity in MCF-7 breast cancer cells [ 37 ]. Moreover, a study also revealed that galloylquinic acid along with doxorubicin, a chemotherapeutic agent, downregulated various oncogenic pathways by remarkably reducing the levels of Notch-1, VEGF, TNF-α, IL-6, cyclin D1, and NFkB, while increasing the activity of capsase-3 in tumour tissues [ 38 ].…”
Section: Introductionmentioning
confidence: 99%